2021
DOI: 10.3390/foods10092232
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Dye-Contaminated Vegetables Using Low-Field NMR Relaxometry

Abstract: Dyeing vegetables with harmful compounds has become an alarming public health issue over the past few years. Excessive consumption of these dyed vegetables can cause severe health hazards, including cancer. Copper sulfate, malachite green, and Sudan red are some of the non-food-grade dyes widely used on vegetables by untrusted entities in the food supply chain to make them look fresh and vibrant. In this study, the presence and quantity of dye-based adulteration in vegetables are determined by applying 1H-nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The use of dyeing agents on food items to make them look fresh and prolong the storage period was analyzed, as this practice harms individuals. 1 H NMR relaxometry [ 8 ] was deployed to determine the presence of Sudan dye, malachite green and copper sulfate on red chili, peas and okra. Homegrown vegetable samples were utilized by spraying the dyes and soaking the vegetables in different solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dyeing agents on food items to make them look fresh and prolong the storage period was analyzed, as this practice harms individuals. 1 H NMR relaxometry [ 8 ] was deployed to determine the presence of Sudan dye, malachite green and copper sulfate on red chili, peas and okra. Homegrown vegetable samples were utilized by spraying the dyes and soaking the vegetables in different solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Shomaji et al [5] reported the use of low-field 1 H-nuclear magnetic resonance (NMR) relaxometry to determine dye contamination on vegetables. It is very well known that non-food-grade dyes could be very toxic.…”
mentioning
confidence: 99%
“…17 It is used to adulterate turmeric powder and Arhar Dal/Pulse (a commonly prepared dish in Indian households) to attract consumers in spite of the fact that it is not permitted by the prevention of food adulteration committee of India. 18 It is reported that the turmeric powder although is valued for its therapeutic properties, can cause serious health consequences when consumed for longer times as a result of the dye contamination. 14,15,[19][20][21] The dye causes oxidative stress in different organs of body including heart, kidney, and liver and damages the neurological systems.…”
mentioning
confidence: 99%